This answer is restricted. Please login to view the answer of this question.

Login Now**First Part:**

First we will proof in (→) direction

“If n is odd then 5n + 6 is odd”

Let n be a positive odd number

Let, n = 2m + 1, where m ∈ Z^{+}

5n + 6 = 5(2m + 1) + 6

= 10m + 5 + 6

= 10m + 11

10m is even and 11 is odd, therefore 10m + 11 is odd.

Thus, if n is odd then 5n + 6 is also odd.

**Second Part:**

Next, we will proof in (**←**) direction

“If 5n+6 is odd, then n is also odd”

Let, 5n + 6 = 2m + 1, where m ∈ Z^{+}

Now, assume n = 2k (n is even) in the above statement

5n + 6 = 10k + 6

10k is even and 6 is even. Therefore, 5n + 6 is also even. But it is contradictory.

Therefore, our assumtion that n is incorrect. thus, n must be odd.

**Final Decision:**

From the above 2 cases we can conclude that if n is a positive integer then n is odd if and only if 5n+6 is odd.

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion